2022
DOI: 10.1101/2022.08.24.505136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted IS-element sequencing uncovers transposition dynamics during selective pressure in enterococci

Abstract: Insertion sequences (IS) are simple transposons implicated in the genome evolution of diverse pathogenic bacterial species. Enterococci have emerged as important human intestinal pathogens with newly adapted virulence potential and antibiotic resistance. These genetic features arose in tandem with large-scale genome evolution mediated by mobile elements. Pathoadaptation in enterococci is thought to be mediated in part by the IS element IS256 through gene inactivation and recombination events. However, the regu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 114 publications
1
12
0
Order By: Relevance
“…In addition to metabolic and MGE system targeting by IS elements, another common iORF was ermF, a macrolide resistance gene that acts by methylating the 23S rRNA subunit to inhibit protein translation (78). We previously found that gentamicin resistance operons are frequently interrupted by IS elements during enterococcal infection (19). We presume that in the absence of antibiotic pressure, bacteria can dampen their effort toward maintaining high-level antibiotic resistance at the population level to favor their fitness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to metabolic and MGE system targeting by IS elements, another common iORF was ermF, a macrolide resistance gene that acts by methylating the 23S rRNA subunit to inhibit protein translation (78). We previously found that gentamicin resistance operons are frequently interrupted by IS elements during enterococcal infection (19). We presume that in the absence of antibiotic pressure, bacteria can dampen their effort toward maintaining high-level antibiotic resistance at the population level to favor their fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic exposure enriches IS insertions in E. faecium during a chronic human infection and antibiotics can stimulate IS element activity in Staphylococcus aureus (19,87). In each of these scenarios this activity was linked to the IS element IS256, which is strongly associated with pathogenic and hospital-associated bacteria (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations